New institutional economics a guidebook - Brousseau, Eric; Glachant, Jean-Michel (Cambridge University Press, 2008)
Institutions frame behaviors and exchanges in markets, business networks, communities, and organizations throughout the world. Thanks to the pioneering work of Ronald Coase, Douglas North and Olivier Williamson, institutions are now recognized as being a key factor in explaining differences in performance between industries, nations, and regions. The fast-growing field of new institutional economics analyzes the economics of institutions and organizations using methodologies, concepts, and analytical tools from a wide range of disciplines (including political science, anthropology, sociology, management, law, and economics). With contributions from an international team of researchers, New Institutional Economics provides theoreticians, practitioners, and advanced students in economics and social sciences with a guide to the many recent developments in the field. It explains the underlying methodologies, identifies issues and questions for future research, and shows how results apply to decision making in law, economic policy, management, regulation and institutional design